CORPORATE ENVIRONMENTAL RESPONSIBILITY AND POLLUTION CONTROL LAWS the case of oil spills... in the niger delta. - Ele, Millicent (ROUTLEDGE, 2026)
This book critically examines the corporate environmental responsibility of major oil companies operating in Nigeria's Niger Delta, focusing on oil spills and comparing regulatory frameworks in Nigeria, the US, the UK, and the EU. It provides a theoretical foundation for holding these companies to the same environmental standards in Nigeria as they adhere to in more advanced jurisdictions.Analysing Shell's oil spill environmental performance data, the book assesses how its operations in Nigeria compare with global performance figures. Additionally, it evaluates Nigerian environmental laws, highlighting deficiencies that may contribute to persistent oil pollution. Furthermore, it explores issues of regulatory capture, corporate environmental crime, and the transnational litigation of Nigerian oil spill cases in the US, the UK, and the EU. The Petroleum Industry Act (PIA) 2021 is comprehensively assessed in the context of corporate environmental governance and oil pollution control.To propose solutions, the book examines legal frameworks for strengthening corporate due diligence and accountability. It advocates for a robust legal regime to address the clean-up liability of pre-existing (stale) oil spills in the Niger Delta, drawing insights from the UK/EU laws on contaminated land, the US Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA or the Superfund), and the UK laws on oil infrastructure decommissioning. Additionally, the book introduces a novel failure to prevent oil spill offence in Nigeria, an omission-based liability inspired by the UK Bribery Act 2010 and the UK Criminal Finances Act 2017.This book will be of interest to researchers and practitioners in the field of environmental law, pollution, and land law.
Keywords: Environmental responsibility -- Nigeria.; Liability for oil pollution damages -- United States.; Liability for oil pollution damages -- Great Britain.; Liability for oil pollution damages -- European Union countries.; Oil spills -- Law and legislation -- United States.; Oil spills -- Law and legislation -- Great Britain.; Oil spills -- Law and legislation -- European Union countries.; Social responsibility of business -- Law and legislation -- United States.; Social responsibility of business -- Law and legislation -- Great Britain.; Social responsibility of business -- Law and legislation -- European Union countries.; elektronické knihy; electronic books